2014
DOI: 10.1096/fj.14-254763
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic mechanism ofNicotiana tabacummyosin‐11 defines a new type of a processive motor

Abstract: The 175-kDa myosin-11 from Nicotiana tabacum (Nt 175kDa myosin-11) is exceptional in its mechanical activity as it is the fastest known processive actin-based motor, moving 10 times faster than the structurally related class 5 myosins. Although this ability might be essential for long-range organelle transport within larger plant cells, the kinetic features underlying the fast processive movement of Nt 175kDa myosin-11 still remain unexplored. To address this, we generated a single-headed motor domain construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 89 publications
2
12
0
Order By: Relevance
“…These results were confirmed by direct experimental modification of a Dictyostelium discoideum myosin (Ito et al, 2009) and also are consistent with a comparison of structural homology models of different myosin motors (Diensthuber et al, 2015). It has been proposed that subtle differences in charge distributions in these two loops, as well as other places within the actin-binding region of myosin XI, also can explain the increased processivity of tobacco myosin XI (Diensthuber et al, 2015), but experimental evidence for this prediction is still missing. Better characterization of the structure-function relationship of myosin motor activities across the spectrum of motor activity will allow us not only to predict the motor properties of uncharacterized myosins but also to manipulate the functions of individual isoforms in a targeted way.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…These results were confirmed by direct experimental modification of a Dictyostelium discoideum myosin (Ito et al, 2009) and also are consistent with a comparison of structural homology models of different myosin motors (Diensthuber et al, 2015). It has been proposed that subtle differences in charge distributions in these two loops, as well as other places within the actin-binding region of myosin XI, also can explain the increased processivity of tobacco myosin XI (Diensthuber et al, 2015), but experimental evidence for this prediction is still missing. Better characterization of the structure-function relationship of myosin motor activities across the spectrum of motor activity will allow us not only to predict the motor properties of uncharacterized myosins but also to manipulate the functions of individual isoforms in a targeted way.…”
supporting
confidence: 74%
“…Targeted mutagenesis of C. corallina motors has revealed that the charge distribution between two surface loops within the actinbinding domain of the motor influences the turnover rate by modulating the rate of ADP release (Ito et al, 2009). These results were confirmed by direct experimental modification of a Dictyostelium discoideum myosin (Ito et al, 2009) and also are consistent with a comparison of structural homology models of different myosin motors (Diensthuber et al, 2015). It has been proposed that subtle differences in charge distributions in these two loops, as well as other places within the actin-binding region of myosin XI, also can explain the increased processivity of tobacco myosin XI (Diensthuber et al, 2015), but experimental evidence for this prediction is still missing.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…donovani parasites adopt metabolic reconfiguration by shift in primary carbon metabolism to subvert oxidative stress posed by antileishmanial drug [34]. The key enzymes of glycolytic pathway [12] and glucose uptake remain unaltered during stress in Leishmania [34].…”
Section: Discussionmentioning
confidence: 99%
“…These remarkable speeds seem to be possible because of subtle changes in the otherwise highly conserved myosin motor ( Ito et al. , 2009 ; Henn and Sadot, 2014 ; Diensthuber et al. , 2015 ).…”
Section: Mechanisms Of Fast Myosin-dependent Movementsmentioning
confidence: 99%